(untitled) (Biological Sciences - PJSIR, 2002)
The dipole rotation and ionic polarisation mechanisms that govern microwave heating were examined in relation to determination of moisture content in visco-elastic material. Samples of pepper were dried by heating in a microwave oven for time duration 5,10,20 and 30 min at different microwave power 350W, 500W and 650W respectively. The moisture content of the samples was determined for specific time and microwave power. The results were compared with standard measurement. Moisture content measurement accuracy in the microwa ve oven was affected by drying time and microwave power.